2016
DOI: 10.3899/jrheum.160592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Longterm Treatment with Bosentan and Iloprost on Nailfold Absolute Capillary Number, Fingertip Blood Perfusion, and Clinical Status in Systemic Sclerosis

Abstract: Objective.To quantify in patients with systemic sclerosis (SSc) the absolute nailfold capillary number/mm (the absolute number of capillaries, observable in the first row, in 1 mm per field) and fingertip blood perfusion (FBP) during longterm therapy with the endothelin receptor antagonist bosentan (BOSE) and the synthetic analog of prostacyclin PGI2 iloprost (ILO) by multiple diagnostic tools. Observed values were correlated with clinical outcomes.Methods.Thirty patients with SSc already receiving intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 40 publications
2
60
0
1
Order By: Relevance
“…Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies . Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day‐to‐day risk index .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies . Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day‐to‐day risk index .…”
Section: Discussionmentioning
confidence: 99%
“…N = number. very good reliability of the software was confirmed, according to results of single measures ICC, in the difficult SSc image subsets, but also in the easier images obtained from healthy subjects and PRP subject subsets, used as controls.Recent evidences, in large SSc cohorts, confirmed that the number of capillaries, as detected by NVC, is the most reliable capillaroscopic parameter for prediction of disease progression and detection of effects of therapies 4,5,42,43. Additionally, capillary density was used for the construction of several scoring systems such as the CSURI, the MES, and the simple day-to-day risk index 4,28,44.…”
mentioning
confidence: 99%
“…Following disease progression, dynamic transition of microvascular abnormalities through different NFC patterns can be found in up to 50% of SSc patients [18,26]. On the other hand, capillaroscopy patterns can improve after up to 4 years of combined treatment, revealing a progressive significant recovery in structure and function of microcirculation, associated to ameliorated outcomes, independently of disease severity [27][28][29].…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 99%
“…In addition, the NVC patterns have been found to change in patients with SSc with up to 4 years of combined therapy, in particular showing a progressive significant recovery in structure as well as function of microvasculature, linked to improved clinical outcomes, independent of disease severity [20][21][22].…”
Section: The Scleroderma Pattern In Systemic Sclerosismentioning
confidence: 99%